ANALISIS PEMANGKU KEPENTINGAN DALAM KEBIJAKAN PENGELOLAAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KEHUTANAN - Nurtjahjawilasa Nurtjahjawilasa; Hariadi Kartodihardjo; Dodik Ridho Nurrochmat; Agus Justianto (Jurnal Analisis Kebijakan Kehutanan, 2015)
Management and development of forestry human resources is very important on attaining the objectives of forestry development towards sustainable forest management (SFM) and prosperous society. Lack of proper policy on forestry human resources management and development may degrade the quality of forest governance. Good understanding of the dynamics of power, interests, knowledge, and networks of stakeholders affecting the structure and performance of forestry human resources and it can be done by using an institutional approach to stakeholder analysis framework. This study aimed to determine the parties' interests and influences in policy-making on forestry human resource management and development. The study was conducted using snowball sampling method both in internal and external of the Ministry of Environment and Forestry. It is found that sixteen stakeholders involved in the policy-making on forestry management and human resources development, which can be divided into the groups of: subjects, key players, context setters, and crowds. The existing relationships are cooperation, complementary and conflict. It needs good understanding, clear rules and strong leadership in order to increase the optimal role of stakeholders and to determine human resource management policies and development.